Strategi BAZNAS Menyalurkan Dana Zakat Dalam Pemberdayaan Ekonomi Masyarakat Menengah Di Kecamatan Tanjung Pura - Fitra Alpa Syafira, Ahmad Fuadi, Khairani Sakdiah (Jurnal Pusat Studi Pendidikan Rakyat, 2022)
The role of the Amil Zakat Agency in Langkat Regency in supporting the economic development of MSMEs in Tanjung Pura District, Langkat Regency has been well implemented, namely with the strategy of the Amil Zakat Agency in Langkat Regency through an economic empowerment program and MSME business actors are provided with knowledge about their business and receive attention in the form of revolving capital. Based on this background, the authors are interested in conducting research on the strategy carried out by the Amil Zakat Agency of Langkat Regency in channeling zakat funds by empowering the economy of the middle class in Tanjung Pura District. after making observations and collecting initial data, the authors used qualitative research methods to simplify the process of collecting data through interviews and documentation, making it easier for writers to describe the data. After obtaining data related to the role of the Langkat district amil zakat agency, the authors triangulated the data by comparing the results of the data obtained through interviews with the results of observations about facts in the field. Furthermore, the researchers concluded that the role of Baznas in Langkat Regency in supporting capital for Micro, Small and Medium Enterprises in Langkat Regency had been well realized with the implementation of a program providing capital assistance to MSME entrepreneurs, namely entrepreneur Tikar Purun in Tanjung Pura District Village, Kab. Langkat, which has received venture capital assistance through Baznas Kab. Langkat. Thus the role of BAZNAS in supporting capital for MSME entrepreneurs in Kab. The level has been reached.